2018
DOI: 10.3389/fncir.2018.00080
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Plasticity in One Hemisphere, Control From Two: Adaptation in Descending Motor Pathways After Unilateral Corticospinal Injury in Neonatal Rats

Abstract: An author name was incorrectly spelled as Madelyne Klugman. The correct spelling is Madelyn Klugman. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. Conflict of Interest Statement: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies, the motor representation of the right forelimb in the TBI + sham group with spontaneous recovery was mapped to the RFA (Fig. 3, F and H) ( 16 , 21 ). However, in the TBI + CC7 group, the contralateral cortex showed a wide range of response areas, including the RFA and CFA, at 8 weeks after surgery.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, the motor representation of the right forelimb in the TBI + sham group with spontaneous recovery was mapped to the RFA (Fig. 3, F and H) ( 16 , 21 ). However, in the TBI + CC7 group, the contralateral cortex showed a wide range of response areas, including the RFA and CFA, at 8 weeks after surgery.…”
Section: Resultssupporting
confidence: 89%
“…Animal studies have revealed that neonatally pyramidotomied rats can separately control impaired and healthy forelimbs, mainly due to the development of a new motor representative area of the impaired forelimb in the RFA region of the intact cortex ( 21 ). CSNs in the RFA terminate at all C2 to C7 levels and connect to premotor neurons, mostly innervating the proximal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying models are different, a smaller but significant body of evidence has supported the same approach of inhibiting the contralesional motor cortex in children with PS and HCP (Kirton, 2013b). Substantial preclinical (Martin et al, 2007;Friel et al, 2013;Friel et al, 2014;Wen et al, 2018) and human (Eyre, 2007;Staudt, 2007b) evidence following early brain injury supports a negative association between the relative preservation of ipsilateral corticospinal projections from the contralesional hemisphere to the affected hand and clinical motor function. Targeting these ipsilateral tracts on the contralesional side thus has the potential to improve motor function.…”
Section: Discussionmentioning
confidence: 99%
“…These neuromodulation approaches are based on evolving human and animal models of how the motor system develops following early unilateral injury (Eyre et al, 2007;Staudt, 2007a;Kirton, 2013b;Wen et al, 2018). Excessive preservation of motor control of the affected limb by the contralesional, ipsilateral hemisphere has led to trials trying "inhibitory" stimulation targeting contralesional M1.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recent animal experiments have revealed that the regrowth of ipsilesional descending fibers from the unaffected hemisphere to denervated motor neurons plays a significant role in the restoration of motor function. 12,13 The possible underlying mechanisms include the promotion of CST axonal sprouting in the unaffected hemisphere across the midline into the denervate (affected) area of the spinal cord. 14 However, due to the limited potential for axonal outgrowth in adults, neurological recovery is difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%